2021
DOI: 10.1109/access.2021.3097371
|View full text |Cite
|
Sign up to set email alerts
|

Switched-Capacitor-Inductor Active-Switched Boost Inverters With High Boost Ability

Abstract: This paper proposes a novel topology, named the switched-capacitor-inductor active-switched boost inverter (SCL-ASBI), based on a switched boost inverter (SBI). The proposed SCL-ASBI allows a high voltage gain with fewer components used in the impedance network. It can be extended to an n-cell by adding one inductor, one diode, and two capacitors for further improving the boost capability. A comparative analysis between the proposed SCL-ASBI topology and four different topologies based on the SBI is presented.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…As can be observed, the suggested topology has the lowest average SDP value, with the exception of [16]. In addition, its peak SDP value is smaller than [22] and [18]. The obtained results indicate that the proposed topology is a cost-effective and SDP-compliant option.…”
Section: F Switching Device Power (Sdp) Calculation and Comparisonmentioning
confidence: 69%
See 3 more Smart Citations
“…As can be observed, the suggested topology has the lowest average SDP value, with the exception of [16]. In addition, its peak SDP value is smaller than [22] and [18]. The obtained results indicate that the proposed topology is a cost-effective and SDP-compliant option.…”
Section: F Switching Device Power (Sdp) Calculation and Comparisonmentioning
confidence: 69%
“…As with voltage stresses, the proposed topology has excellent performance in this instance. In the meantime, although the shoot-through current of the proposed topology like [22] is greater than that of the others, it has the lowest current stress in the additional switch, which reduces the switch losses and improves efficiency.…”
Section: Comparison Of the Current And Voltage Stressmentioning
confidence: 98%
See 2 more Smart Citations
“…The number of elements in the conventional and proposed topologies is provided in Table 2. Based on this Table, it is observed that topologies in [8–9], [17] and [31–32], despite a lower boost factor than the proposed topology, have more storage elements in their Z‐source networks. In topologies presented in [4], [23], and [25–26], the number of storage elements is equal to the proposed topology.…”
Section: Comparison Of the Proposed Topology With The Conventional To...mentioning
confidence: 99%